Demographic and Regional Differences in Household Dietary Diversity in Bangladesh: Evidence from the 2010 Household Income and Expenditure Survey - Akheruzzaman, Md; Ali, Masum; Karim, Kazi Muhammad Rezaul; Amin, Md Ruhul (Bangladesh Journal of Nutrition, 2021)
The dietary diversity score is now being widely accepted as a tool to see the dietary intake pattern qualitatively. This tool can be used for a rapid proxy measure of household food access of the population. As the Household Income and Expenditure Survey of Bangladesh (HIES) are done routinely in many developing countries, this can be a good source of dietary data for the field of nutrition research. The study endeavoured to measure household dietary diversity scores (HDDs, 0-12) from a nationally representative population and frequency of food group consumption for the Bangladeshi population at different spatial levels from the HIES, 2010 dataset. The study found HDDs (Mean±SD) of 6.16±1.91 for Bangladeshi households. Households from Small Municipality Area(SMA) showed the highest HDDs of 6.95±2.34 followed by municipality (6.61±2.04) and rural areas (5.87±1.72).Chittagong and Sylhet division’s households’ diet is more diversified (7.09±2.12 and 6.95±1.83, respectively),whereas the lowest HDDs are found in Rajshahi (5.71±1.68). Mean differences of HDDs significantly vary by the education level of the mother, family size, number of earners, and religious status of the household. Overall, the percentages of households with no intake of meat and poultry, fruits, and milk and milk products were43.1%, 28.2%, and 48.6%, respectively, in the survey period of 14 days. HDDs varies significantly by region and household characteristics. Animal-sourced foods (meat and poultry, milk and milk products, and eggs) and fruits should be made more accessible through policies and programs at the household level across divisions where consumption is low. Bangladesh J. Nutr. Vol. 34, December 2020, P: 87-98